Differences in environmental microbial community responses under rice-crab co-culture and crab monoculture models under cyanobacterial bloom - Tong, Li; Jun, Ling; He, Jiang; Min, Yang; Guoqing, Duan; Yuting, Hu; Huaxing, Zhou; Huan, Wang; Tingshuang, Pan (Frontiers in Microbiology, 2024)
Cyanobacterial blooms (CBs) present significant challenges to Chinese mitten crab (CMC) culture, posing hazards to the aquatic microbial ecology. However, the current focus on the microbial ecological changes within the CMC culture system under the influence of CBs is somewhat insufficient. There's an urgent need to analyze the microbial ecosystem of the CMC culture system under CBs. This study employed 16S rRNA gene amplicon sequencing to investigate the dynamics of the environmental microbial community in both the rice-crab co-culture (RC) and crab monoculture (CM) models. The results revealed that cyanobacteria reached high levels in the CM water in July, while they began to increase in the RC water in August. Notably, OTU147 (uncultured bacterium g_Planktothrix NIVA-CYA 15), identified as the dominant taxon associated with CBs, showed a significant linear relationship with TP, NO2 --N, and the N:P ratio. TP, TN, NO2 --N, and CODMn had a more pronounced impact on the structure of bacterial communities and cyanobacterial taxa in the water. The bacterial community structure involved in carbon metabolism displayed temporal succession in the water. The co-occurrence network of the bacterial community primarily consisted of Chloroflexi, Proteobacteria, and Firnicutes in the sediment, and Actinobacteria, Proteobacteria, Chloroflexi, and Bacteroidota in the water. In contrast, the co-occurrence network included different peripheral species in the sediment and water.Keystone species were predominantly represented by OTU22 (uncultured actinobacterium g_ hgcI clade) and OTU12 (uncultured Opitutae bacterium g_ norank) in the RC water, and by OTU25 (uncultured bacterium g_ Limnohabitans) in the CM water. TP, TN, NO2 --N, and CODMn were identified as the primary environmental factors influencing these keystone taxa within the culture water. In conclusion, this study on the microbial ecology of the CMC culture system under the influence of CBs provides valuable insights that can be instrumental in subsequent management efforts.